2023
DOI: 10.3389/feart.2022.1023883
|View full text |Cite
|
Sign up to set email alerts
|

Upper bound analysis of the anti-seismic stability of slopes considering the effect of the intermediate principal stress

Abstract: Considering the intermediate principal stress effect of soils, the unified strength theory was applied to correct the shear strength index of soils. Based on a mechanical model of the anti-seismic stability of slopes, the analytical formula of the stability coefficient was deduced by the upper bound method and the quasi-static method. Then the optimal solution of the stability coefficient was figured out via the Matlab software. The result shows that, if the intermediate principal stress is ignored, the shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…However, current strength discount method mainly adopts Mohr-Coulomb strength criterion. It does not consider the influence of the IPS on the stability and damage mode of the rock slope [20]. YOU et al [21] found that the IPS has a certain impact on the strength of rock, and the influence degree of the IPS on the strength of rock materials is approximately 15%.…”
Section: Introductionmentioning
confidence: 99%
“…However, current strength discount method mainly adopts Mohr-Coulomb strength criterion. It does not consider the influence of the IPS on the stability and damage mode of the rock slope [20]. YOU et al [21] found that the IPS has a certain impact on the strength of rock, and the influence degree of the IPS on the strength of rock materials is approximately 15%.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of slopes has long been a complex geotechnical issue in the field of engineering and has received extensive research and attention. Currently, analyses and research on slope stability are still theoretically lagging behind practice, and the accuracy of evaluations depends on the specific circumstances [5] [6] [7] [8] [9]. To address slope instability and failure problems, numerous slope evaluation methods have been proposed.…”
Section: Introductionmentioning
confidence: 99%